P191 Can real-time data collection improve mortality and delivery of acute non-invasive ventilation (NIV)?. (12th November 2019) - Smith, DP; Boast, LA; Kempster, L; Allen, S; Wyatt, J; Roberts, ME; Molyneux, AW
Abstract : Introduction: The NCEPOD Acute NIV report, Inspiring Change (2017), showed that major improvements were required. Despite high mortality (35%), fewer than half of hospitals routinely audited their own practice. NCEPOD and BTS Quality Standards recommend performance targets and governance arrangements. Nationally NACAP collects only limited data on NIV and is not consistent with BTS quality standards; there have been only 4 BTS NIV audits in a decade. In contrast MINAP/NICOR and SSNAP mandate continuous data collection in STEMI and acute stroke, driving improved delivery of care and benchmarking. Previously we demonstrated methods for improving NIV delivery and capacity with an acute NIV prescription and NIV service quality dashboard. We propose a Patient Quality Dashboard to continuously monitor and feedback individual patient care. Methods: To measure delivery of care we developed a 9-point scoring system designed to be administered at the first consultant NIV review, based upon 8 objective and 1 subjective criteria. This was linked with clinical coding to audit performance, length of stay (LoS), and mortality. This data is presented at our Quarterly NIV morbidity and mortality (M&M) meetings to identify further areas requiring improvement. Utilising dashboard data, we email personalised scores as feedback to the clinicians commencing NIV with references to further learning. Results: Since inception in 2018/19 189 patients have been admitted, median LoS 7 days; mortality rates have fallen significantly from 24.5% (2016/17) to 10.1%, (p=0.0005) (See table 1). Dashboard scores of 104 patients show good performance with a median score of 6.9/9 (SD 1.58), significantly improving from Q1-Q4 (ANOVA, p=0.12328), although only 61.5% received NIV within BTS quality standard guidance. We have sent 42 feedback emails to clinicians and conducted four M&M meetings. Conclusions: We have demonstrated that a Patient Quality Dashboard, integrated with ward round documentation and an NIV prescription allows sustainable, continuous routine data collection automating auditing against BTS quality standards. Continuous audit facilitates clinician feedback and monitoring performance via M&M meetings, and may be associated with a significant fall in mortality. We propose this as a potential National model to improve care for patients receiving Acute NIV, as per MINAP/SSNAP.